2020
DOI: 10.1002/micr.30692
|View full text |Cite
|
Sign up to set email alerts
|

Use of soleus musculocutaneous perforator‐based propeller flap for lower extremity wound coverage after osteocutaneous fibula free flap harvest

Abstract: Background Osteocutaneous fibula free flap (OCFFF) donor sites are often covered with skin grafts, with an additional donor site, more postoperative care, and increased cost. The authors examine posterior tibial artery (PTA) based pedicled propeller flaps (PPF) as an alternative for OCFFF donor site coverage. Patients and methods Retrospective review of 16 consecutive patients from 30 to 79 years old, who underwent OCFFF reconstruction of head and neck defects (11 mandibular, 5 maxillary), with the closure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The basis of the propeller flap in this area is either perforators from the PA or PTA, in the form of either septocutaneous perforators or musculocutaneous perforators via the soleus muscle. Both Kaleem et al 28 and Sharma et al 29 demonstrated the use of the soleus musculocutaneous perforators stemming from the PTA as the basis of these perforator flaps, while Morgan et al 30 described the use of perforators from the PA, advocating that proactively identifying these perforator vessels during OCFFF harvest expanded the pool of candidates for closure using PFPFs. While the use of perforators from the PA may be technically easier, this depends on the length of pedicle needed for the OCFFF, given that an attempt to maintain a perforator off the PA system for a propeller flap may result in a shortened vascular pedicle for the fibula flap, thus depends on the take‐off point of the PA‐based perforator.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the propeller flap in this area is either perforators from the PA or PTA, in the form of either septocutaneous perforators or musculocutaneous perforators via the soleus muscle. Both Kaleem et al 28 and Sharma et al 29 demonstrated the use of the soleus musculocutaneous perforators stemming from the PTA as the basis of these perforator flaps, while Morgan et al 30 described the use of perforators from the PA, advocating that proactively identifying these perforator vessels during OCFFF harvest expanded the pool of candidates for closure using PFPFs. While the use of perforators from the PA may be technically easier, this depends on the length of pedicle needed for the OCFFF, given that an attempt to maintain a perforator off the PA system for a propeller flap may result in a shortened vascular pedicle for the fibula flap, thus depends on the take‐off point of the PA‐based perforator.…”
Section: Discussionmentioning
confidence: 99%
“…Although the spindle‐shaped FTSG method is commonly used, other local FTSG methods such as double‐opposing VY closure (Squadrelli‐Saraceno et al, 2010) and combined semi‐elliptical FTSG (Shimbo et al, 2019) have also been described. More recent studies have discussed propeller perforator flap methods (Feng et al, 2020; Kaleem et al, 2021; Morgan et al, 2020; Sharma et al, 2013). In the present systemic review, we compared outcomes including adapted free fibula flap size and postoperative complications among FTSGs, STSGs, and flaps for the closure of free fibula flap defects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers have proposed several local closure methods harvesting from ipsilateral lower leg for avoiding secondary donor sites, including local skin graft methods and flap methods. These closure methods are divided into three groups, each with its advantages and disadvantages: FTSG (Akashi et al, 2016; Shimbo et al, 2019; Squadrelli‐Saraceno et al, 2010; van der Lei et al, 2008; Wang et al, 2016), STSG (Kim et al, 2008; Olson et al, 2015), and flap methods (Feng et al, 2020; Kaleem et al, 2021; Morgan et al, 2020; Sharma et al, 2013). Although the STSG method is applicable to the largest free fibula flap size, because the STSG area is approximately correlated with that of the free fibula flap, there is still uncertainty regarding the largest size of a free fibula flap defect which can be addressed using the FTSG and flap methods.…”
Section: Introductionmentioning
confidence: 99%
“…Using a propeller design, a portion of the flap (the major blade) is transferred to resurface the defect, and the other portion (the minor blade) is placed over the donor site of the major blade, facilitating its direct closure 12 . Propeller flaps are now widely used for reconstruction in various parts of the body 13,14 . Any skin island flap can become a propeller flap 12 .…”
mentioning
confidence: 99%
“…12 Propeller flaps are now widely used for reconstruction in various parts of the body. 13,14 Any skin island flap can become a propeller flap. 12 Furthermore, if pivoted around its source vessel, any myocutaneous flap could be regarded as a muscle-pedicled propeller flap; for example, the vertical rectus abdominis myocutaneous flap, which is generally rotated around its deep superior epigastric vascular pedicle at the costal margin.…”
mentioning
confidence: 99%